2021
DOI: 10.1038/s41598-021-84314-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of percutaneous vertebroplasty with high-viscosity cement in the treatment of severe osteoporotic vertebral compression fractures

Abstract: Severe osteoporotic vertebral compression fractures (OVCFs) were considered as relative or even absolute contraindication for vertebroplasty and kyphoplasty and these relevant reports are very limited. This study aimed to evaluate and compare the efficacy of vertebroplasty with high-viscosity cement and conventional kyphoplasty in managing severe OVCFs. 37 patients of severe OVCFs experiencing vertebroplasty or kyphoplasty were reviewed and divided into two groups, according to the procedural technique, 18 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…It has been widely used in treating OVCF in the thoracolumbar spine with proven efficacy, becoming the gold standard for treating OVCF patients ( 2 , 3 ). The mechanism of vertebroplasty is to fix microfractures and enhance the stability of the vertebral body by injecting bone cement into the vertebral body ( 4 ). Thus, the distribution of bone cement in the vertebral body is linked to clinical efficacy ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in treating OVCF in the thoracolumbar spine with proven efficacy, becoming the gold standard for treating OVCF patients ( 2 , 3 ). The mechanism of vertebroplasty is to fix microfractures and enhance the stability of the vertebral body by injecting bone cement into the vertebral body ( 4 ). Thus, the distribution of bone cement in the vertebral body is linked to clinical efficacy ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies displayed the change in Cobb's angle before and after surgery. Among them, one study (114 cases) 19 reported no significant difference for both groups, four studies (341 cases) 21,23,25,27 reported significant differences for both groups, and two studies (166 cases) 22,26 reported significant differences in favour of PKP. We extracted Cobb's angles at two time points for analysis according to data available.…”
Section: Resultsmentioning
confidence: 98%
“…TSA was performed to determine whether the present evidence was reliable and conclusive. During TSA, the study of Li et al 27 . was automatically ignored due to the very small sample size (<20 for each group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The operation was performed following the methods described by Li et al (14). Bucinnazine was routinely injected 30 minutes before surgery, and electrocardiogram monitoring was conducted throughout the operation.…”
Section: Surgical Methodsmentioning
confidence: 99%